GAYA BAHASA DALAM KUMPULAN PUISI QASIDAH JERUJI NURANI KARYA M. ROIS RINALDI (STYLISTICS IN GROUPING POETRY QASIDAH JERUJI NURANI BY M. ROIS RINALDI) - Adek Dwi Oktaviantina (Kadera Bahasa, 2018)
Poetry created by a process of creations which is involving the idea from the owner of the words. Stylistic is a model that speak inside the poetry. M. Rois Rinaldi is the owner of the words who uses stylistic in the creation process. This formulation of research is how stylistics in grouping poetry of Qasidah Jeruji Nurani by M. Rois Rinaldi. The aim of research is describing the stylistics in grouping poetry of Qasidah Jeruji Nurani by M. Rois Rinaldi. This research methods are qualitative. Qasidah Jeruji Nurani by M. Rois Rinaldi is indirectly an expression according to Riffatere, because of three main reasons, the first is displacing of meaning, the second one is distorting of meaning, and the last is creating of meaning. The conclussion of this research is the poetry of M. Rois Rinaldi entittled ‘Kelak’, ‘Membaca Wajah’, and ‘Secabik Senja’ has a specific metaphor about the game of life and death.